2005
DOI: 10.1111/j.1445-5994.2004.00742.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of health‐related quality of life in institutionalised older persons in northern Sydney

Abstract: It is recognised that the focus of health-care interventions for frail older persons should not be restricted to increasing longevity, but should encompass measures aimed at improving or maintaining the health-related quality of life (HRQoL) of these individuals. We studied the HRQoL profile of 612 frail older persons residing in nursing homes and hostels in northern Sydney, Australia, and sought to ascertain some of the factors that affect their perceived quality of life. Our findings suggest that common heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 21 publications
(19 reference statements)
4
23
0
1
Order By: Relevance
“…This finding is in accordance with a large epidemiologic study in US nursing homes reporting that patients with UI experienced lower quality of life in the domains of dignity, autonomy and mood [23], and a study in Australian nursing homes and hostels showing that loss of dignity and independence caused by UI was strongly associated with quality of life [24]. An interview-study with older female residents residing in nursing homes with UI in Canada indicated that they felt regression to childhood and embarrassment, which led to loss of control, dignity, independence, and decision-making power [25].…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in accordance with a large epidemiologic study in US nursing homes reporting that patients with UI experienced lower quality of life in the domains of dignity, autonomy and mood [23], and a study in Australian nursing homes and hostels showing that loss of dignity and independence caused by UI was strongly associated with quality of life [24]. An interview-study with older female residents residing in nursing homes with UI in Canada indicated that they felt regression to childhood and embarrassment, which led to loss of control, dignity, independence, and decision-making power [25].…”
Section: Discussionsupporting
confidence: 90%
“…A study reported that up to 94% of nursing home residents spend their time sitting or lying down, in spite of the fact that some of them are capable of independent activities such as walking [30]. Studies have suggested that greater dependency due to physical and mental impairment among institutionalised older people is inversely related to health-related QoL [16,31,32]. …”
Section: Introductionmentioning
confidence: 99%
“…Exploring the domains and degrees of functioning and well-being that are affected by the frailty of elders will help clinicians to understand the impact of frailty on functional status and well-being. Previous studies have investigated the impact of frailty on HRQOL, and findings have been reported for community-dwelling elders referred to an outpatient geriatric service [13], patients with heart failure [14], older adults with cardiometabolic risk factors [15], institutionalized older persons [16] or older Mexican Americans [17]. Although the effect of frailty had been examined in community-dwelling older adults in the Netherlands [18] or in Mexican Americans [17], this line of study has never been conducted in Chinese.…”
Section: Introductionmentioning
confidence: 99%